KOMUNIKASI INSTRUKSIONAL DIVISI SAFETY HEALTH AND ENVIRONMENT DALAM UPAYA MENCEGAH TERJADINYA KECELAKAAN KERJA DAN PENYAKIT AKIBAT KERJA DI EMP MALACCA STRAIT, S.A. - ", Nurhasanah; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The competition in the economic sector is very diverse, especially in the industrial world in order to ensure the sustainability of the business, many companies no longer rely on marketing strategies, but also to prevent the occurrence of losses on aspects of occupational safety and health (OSH) and environmental protection. EMP conducts Instructional Communication activities that are implemented in SHE Talk activities, ie Toolbox Meeting and Pre Job Safety Meeting prior to perform the work at field. This study aims to determine the credibility of communicators, what are methods and instructional communication media used in SHE Talk activities as an effort to prevent the occurrence of occupational accidents and illness.This research uses qualitative research with descriptive approach. The subjects consisted of 9 persons selected using Purposive Sampling technique, based on predetermined criteria.. Data collection techniques in this study with in-depth interviews, non-participant observation and documentation. The technique of data validity in this research is extension of participation and triangulation.The results showed that the credibility of communicators can be seen from the expertise. Safety Officer, must follow some International qualifications, one of them is OHSAS 18001: 2007 Certified Lead Auditor, and follow Modern Safety Management Training to become Supervisor and Superintendent. In addition, the belief that is visible from the assertive and clear attitude when leading the activities of meeting toolbox and pre job safety meeting and have extensive knowledge. Instructional communication method used the command , question and answer method, where Safety Officer, Superintendent and Supervisor lead this activity by giving directions about what work will be done today, what are the risks, and how to prevent accident. Instructional communication media used is audiovisual media, namely laptops and other media aids.Key Word: Instructional Communication, Safety, Accident and Work Related Illne